Pour une sociologie des ordres juridiques - Rocher, Guy (Les Cahiers de droit, 1988)
The object of the sociology of law has to date been defined too narrowly. Positive law as conceived by jurists, that is law related to the State in one way or another through the legislator, the courts or the law itself, has generally been recognized as the object of the sociology of law. Sociology of law has therefore remained too much within the legal ideology that dominates not only the legal profession but the overall culture of modern Western societies. It is suggested that the notion of "legal order" should furnish the appropriate object for the sociology of law, provided it is defined broadly enough to cover all the legal orders existing in a given society. This first requires a definition of law not only in terms of norms, rules and principles, but as a living institution that includes all agents and/'or organizations that contribute to produce, interpret and apply the law. And secondly, it requires considering State legal order as just one of all the legal orders that co-exist in a society. It should be sociology's task to identify the numerous non-State legal orders and to analyse the complex set of interrelationships among them and with the State legal order. This broadened pluralistic line of thought follows the leads provided long ago by Max Weber and Santi Romano, which have not to date been paid all the attention they deserve.